The Effect of Various Doses of Rice Straw Mulch on the Growth and Production of Beans (Phaseolus Vulgaris L.) - Wa Ode Anti; Abdul Rahim; Wa Ode Erni (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
The purpose of this research was to determine the effect of rice straw mulch and to determine the amount of rice straw mulch that had the best impact on the growth and production of green beans (Phaseolus vulgaris L.). The research was conducted in Lamorende Village, Tongkuno District, Muna Regency, from February to April 2020. Compilation based on a Randomized Block Design (RBD) with one factor consisting of 4 (four) treatment levels, namely M0 = control (without rice straw mulch), M1 = the amount of rice straw mulch 5 tons ha-1 equivalent for 1.2 kg plots - 1, M2 = size of rice straw mulch 10 tons ha-1 is equivalent to 2.4 kg plot-1 and M3 = size of rice straw mulch 15 tons ha-1 is equivalent to 3.6 kg plot-1. From these treatments, they were divided into three groups to obtain 12 experimental units. Observation data from each parameter were analyzed using Analysis of Variance (ANOVA). As for the hypothesis using the F test at the 95% confidence level. The results showed that the treatment of straw mulch dose significantly affected the plants, the number of leaves, the number of pods per plant, pod weight per plant, and the productivity of green beans. Rice straw mulch treatment at a rate of 15 tonnes ha-1, gave the best growth and production.